Galactic Cosmic Ray Variability at Two Neutron Monitors: Relation to Kp Index. (24th February 2015) - Okpala, Kingsley Chukwudi
Abstract : The average characteristics of year-to-year variability of Galactic cosmic ray (GCR) flux measured in one mid-latitude neutron monitor stations (Newark) and high latitude station (Apatity) have been studied under different planetary disturbance (Kp) conditions. The year-to-year variability which oscillates in response to solar cycle was analyzed using Fourier technique and the amplitude of variation was obtained using data for 1980–2005. There is a noticeable trend in the difference between the amplitudes of the year-to-year variation of the two stations. The difference is highest during low Kp conditions and lowest during high Kp condition. There is generally lesser association of GCR with solar wind (SW) flow pressure and density as the Kp index increases. Similar feature is observed with the interplanetary magnetic field IMF (total). These observations have important implications for our present understanding of the effect of solar activity to variability in GCR flux.